IOT BASED SOLAR POWERED PUMP FOR AGRICULTURAL IRRIGATION AND CONTROL SYSTEM - Okomba, Nnamdi S.; Esan, Adebimpe O.; Omodunbi, Bolaji A.; Sobowale, Adedayo A.; Adanigbo, Opeyemi O.; Oguntuase, Oluwasegun O. (FUDMA JOURNAL OF SCIENCES, 2023)
This paper focuses on the implementation of a solar-powered pump system integrated with IoT technology for agricultural irrigation control. By leveraging the properties of the system, such as humidity, temperature, soil moisture, time collection based on solar panel activity, and peculiarities like using a mobile app and automated control, the project aims to provide an efficient and sustainable solution for irrigation.The system utilizes humidity sensors strategically placed in the soil to monitor moisture levels, enabling precise irrigation control. To enhance user experience and accessibility, a user-friendly mobile app is developed. This app allows farmers to remotely monitor and control the irrigation process, providing real-time data, irrigation scheduling options, and the ability to adjust system settings. Through IoT integration, the system enables automated control of the pump based on predefined parameters. By analyzing sensor data, including humidity levels and solar panel activity, the system autonomously adjusts irrigation operations, reducing manual intervention and improving overall efficiency. From the acquired results, at a temperature of 37.2 0C, the humidity level is low at 49.6%, thereby activating the irrigation pump which resulted to decrease in  temperature at 26.70C after a period of 1hr 48mins with the humidity, and soil moisture levels at 73.9%, and 88% respectively.  The developed system monitors and balance the soil moisture level through automated irrigation process which is solar powered and remotely managed.